Territorial Marketing Applied of Great Events: The Case Study of Cortina d’Ampezzo - Silvia Fedrici; Elisa Rancati (European Scientific Journal, ESJ, 2021)
Territorial marketing and great events marketing is generally considered by academics and professionals as a discipline with dynamic and not fully distinct fields. This study aims to develop research in these fields, examining the impacts of territorial marketing on a tourism destination during a great event. Data collected from tourists in Cortina d’Ampezzo (Italy) demonstrates that this destination became famous following territorial marketing used for the Olympic Games in 1956 and its attractiveness is still alive, so much so that it has been chosen once again to host the 2026 Winter Olympic Games. This study underlines how territorial marketing has created a tourism destination that can attract tourists regardless of the great event.